Performance of Traditional Ansamble - Rakhimov Sayfudin Shokirjonovich (International Journal on Integrated Education, 2021)
This article attempts to cover a scientific body of information about the ensemble. Both the traditional ensemble and the subtleties of the performance skills are shown. The ensemble's performance also highlighted the leader's managerial skills.